2020
DOI: 10.21203/rs.3.rs-36868/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of meteorological factors on the activity of influenza in Chongqing, China, 2012–2019

Abstract: Background: The effects of multiple meteorological factors on influenza activity remain unclear in Chongqing, the largest municipality in China. We aimed to fix this gap in this study.Methods: Weekly meteorological data and influenza surveillance data in Chongqing were collected from 2012 to 2019. Distributed lag nonlinear models (DLNMs) were conducted to estimate the effects of multiple meteorological factors on influenza activity.Results: Inverted J-shaped nonlinear associations between mean temperature, win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
(30 reference statements)
2
5
0
Order By: Relevance
“…In this study, it was found that temp, DTR, RH and SD were significantly associated with Flu-A and Flu-B based on different time lags which were similar to previous studies conducted in neighboring cities ( Zhang et al., 2020 ; Ma et al., 2021 ; Qi et al., 2021 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, it was found that temp, DTR, RH and SD were significantly associated with Flu-A and Flu-B based on different time lags which were similar to previous studies conducted in neighboring cities ( Zhang et al., 2020 ; Ma et al., 2021 ; Qi et al., 2021 ).…”
Section: Discussionsupporting
confidence: 89%
“…The model was used for each meteorological variable including temp, DTR, RH, and SD. The maximum lag day was defined as 27 days, which was based on the incubation period of influenza and potential lagged effects revealed by previous studies ( Guo et al., 2019 ; Qi et al., 2021 ). Akaike information criterion (AIC) was used to select the dfs for the meteorological variable in each model and the lowest AIC score was the most fitted model.…”
Section: Methodsmentioning
confidence: 99%
“…This founding was similar with previous studies. (9,22) One hypothesis was that the lack of sunshine reduced the synthesis of melatonin and vitamin D in the body, which decreased human immunity. (37) Melatonin could activate intracellular signalling pathways and transcription factors, thereby inhibiting in ammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum lag day was de ned as 27 days, which was based on the incubation period of in uenza and infectious period of in uenza virus from the previous studies. (12,22) Akaike Information criterion (AIC) was used to select the dfs for meteorological variable in each model and the lowest AIC score was the most tted model. The AIC values were summarized in Table S1.…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, at an AT of-5.35°C, the risk of in uenza incidence was highest, and AT was negatively correlated with in uenza incidence in all age groups. Several studies have shown that temperature changes signi cantly impact in uenza transmission and that the relative risks (RRs) of in uenza activity increase with the decrease in weekly AT, and the in uenza infection rate decreases by 1.1% for every 1°C increase [24,25]. Another study has shown that for in uenza A or B, the temperature and the incidence of in uenza have a non-linear negative correlation.…”
Section: Discussionmentioning
confidence: 99%